HUBUNGAN ANTARA PENGETAHUAN TENTANG PROSES MENUA DENGAN TINGKAT DEPRESI PADA LANSIA DI DESA MAJASTO SUKOHARJO - Dinar Ariasti; Joko Sutrisno (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2016)
AbstractThe role of knowledge in dealing with depression is to help individuals recognize theexistence in this world by expanding self-awareness, find himself again and is responsiblefor the direction of his life. Initial survey results indicate that the 3 (three) respondenexperienced the characteristics of someone who is depressed by the low level ofknowledge. The purpose of this study was to determine the relationship of knowledgeabout the aging process with a level of depression in elderly Majasto Village, DistrictTawangsari, Sukoharjo.Subject of this study was elderly people in the village Majasto, based on an initial surveyfound as many as 65 elderly. This research method in this study an analytic correlationwith cross sectional approach. Data collection tool used is a questionnaire to measure thelevel of knowledge of the aging process with depression from Majasto village.Results of the study there were respondents with a high level of knowledge nothing isseverely depressed, two respondents had moderate depression and 10 respondents didnot experience depression and 3 respondents with a low level of knowledge into a deepdepression and 2nd respondents had moderate depression. the results of Chi-Square testwith SPSS version 18.0 with Î± = 5% (0:05) was obtained p <0.001 to p value of <0.05,which means that Ho refused and Ha accepted. Conclusion of this study there is arelationship between the level of knowledge about the aging process with a level ofdepression in residents in the village Majasto Tawangsari Sukoharjo.Keywords: knowledge, depression